2021
DOI: 10.1038/s41598-021-99173-4
|View full text |Cite
|
Sign up to set email alerts
|

Versatilely tuned vertical silicon nanowire arrays by cryogenic reactive ion etching as a lithium-ion battery anode

Abstract: Production of high-aspect-ratio silicon (Si) nanowire-based anode for lithium ion batteries is challenging particularly in terms of controlling wire property and geometry to improve the battery performance. This report demonstrates tunable optimization of inductively coupled plasma reactive ion etching (ICP-RIE) at cryogenic temperature to fabricate vertically-aligned silicon nanowire array anodes with high verticality, controllable morphology, and good homogeneity. Three different materials [i.e., photoresist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 84 publications
(80 reference statements)
0
29
0
Order By: Relevance
“…The chemical solution process involves complicated synthesis routes such as formation of solid catalyst seeds on the substrate, and requires precise control of the process parameters, such as temperature, for 1D structure formation. Refino et al reported vertical Si nanowire array anodes created in a top-down process by plasma etching 9 . Si nanowire arrays were fabricated by applying circular patterns to Si wafers as a template using photolithography, where an n-type Si wafer with high electrical conductivity was used as the active anode material.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical solution process involves complicated synthesis routes such as formation of solid catalyst seeds on the substrate, and requires precise control of the process parameters, such as temperature, for 1D structure formation. Refino et al reported vertical Si nanowire array anodes created in a top-down process by plasma etching 9 . Si nanowire arrays were fabricated by applying circular patterns to Si wafers as a template using photolithography, where an n-type Si wafer with high electrical conductivity was used as the active anode material.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared to the Bosch process, which suffers from scalloping effects on the etched structures, ICP-RIE conducted at cryogenic temperatures can produce vertical Si NW arrays with high aspect ratios and smooth sidewalls [27]. Although high-aspect-ratio Si nanowires have been successfully produced by photolithography and cryogenic ICP-RIE, their use in LIBs is rarely reported [28].…”
Section: Introductionmentioning
confidence: 99%
“…There are various forms of RIE, such as inductively coupled plasma reactive ion etching (ICP) RIE, deep reactive ion etching (DRIE), cryogenic DRIE, and Bosch DRIE. These RIE techniques are used to micro-fabricate silicon hollow micro-needles with smooth tapering [ 107 ], organic semiconductors with high-resolution displays [ 108 ], the optimization of high-aspect-ratio vertical Si nano-wire anodes for lithium-ion batteries [ 109 ], and the high fidelity and low roughness of SiC substrates for bulk acoustic wave resonators [ 110 ], investigate etching induced damage in p-type GaN at low temperatures [ 111 ] and the isotropic silicon etching of MEMS [ 112 ]. The process has some drawbacks, however, including being expensive because of the use of complex equipment, controlled conditions, and sidewall defects.…”
Section: Alternative Micro-feature Fabrication Processesmentioning
confidence: 99%